ЦИКЛ «ПАРНАС» ВІТАЛІЯ МАНИКА ДЛЯ СКРИПКИ СОЛО: ПРОГРАМНИЙ СЮЖЕТ ІЗ АНТИЧНОЇ МІФОЛОГІЇ В СУЧАСНІЙ ІНТЕРПРЕТАЦІЇ - Климбус Ірина Михайлівна (World Science, 2019)
Vitali Manyk is a modern composer from Ivano-Frankivsk who productively works in various music genres. He is the author of works for symphony orchestra, vocal and chamber instrumental tracks, music background of theatre performances. Lack of critical analysis of his art has caused the topicality of this article. Its main objective is to reveal basic features of the programming principle application in the «Parnassus» cycle which consists of nine pieces for violin solo. Having chosen the figurative music plot which originated from Ancient Greece, V. Manyk declares his interest in European civilization and artistic attainment. On the other hand, he tends to synthesize arts. As you know, the phenomenon of synthesis of the arts also comes from antiquity. According to the Greek mythology, Parnassus is the home of gods and also the residence of the nine muses – the patronesses of arts and sciences. The first piece «Clio» (the muse of history) is aimed at improvisation. At the same time the author accompanies every miniature with remarks concerning instrumentation, manner, tempo, rhythm, provides detailed notes as to the sound dynamics, etc. The second piece «Euterpe» (the muse of lyrical poetry and music) is marked by the lack of lilt organization. Music theme has abundant rhythmics, abrupt texture and dynamic changes. The third and the fourth pieces «Thalia» (the muse of comedy) and «Melpomene» (the muse of tragedy) expose quite the opposite images and emotions of the Greek theatre genres. However, the composer applies means of humorous and tragic music spheres of different epochs. The fifth piece «Polyhymnia» (the muse of sacred poetry and pantomime) is based on the intonations of antique chants. Melody develops gradually, has narrow range, but in the middle of the piece reaches significant dramatic effect. The sixth miniature «Urania» (the muse of astronomy) is the illustration of a starry night. Quiet and peaceful sounding dominates, short motives are directed upwards. In the seventh piece «Terpsichore» (the muse of dance and choral singing), with the help of antiphonous sounding of imaginary male and female groups of singers, the author reproduces the model of an ancient syncretic roundelay. The eighth miniature «Erato» (the muse of love lyrics) resembles the second piece (Euterpe) in images’ character and exposition. The last piece «Calliope» (the muse of epos) reflects V. Manyk’s aspiration to generalize the contents of the entire cycle. That’s why short reminiscences of all previous pieces are quite prominent here. The cycle of short miniatures is enriched with the wide range of historic, cultural and even philosophical connotations. Programme plot embodies by means of expression such as improvisation of musical texture, s broad range articulation, characteristic contrast melodies and motifs, the uniqueness semantic structure work.